Amelioration from the ocular irritant Capsaicin: development and assessment of a Capsazepine in situ gel system for ocular delivery. (2nd June 2020) - Krishnatreyya, Harshita; Hazarika, Hemanga; Saha, Achintya; Mandal, Santa; Bora, Nilutpal Sharma; Kishor, Sumit; Bhutia, Yangchen Doma; Goyary, Danswrang; Karmakar, Sanjeev; Chattopadhyay, Pronobesh
ABSTRACT: Background: Defense personnel utilize capsaicin-based ocular sprays as non-lethal agents for law implementation during instances of mob violence. This study involves the capsaicin antagonist Capsazepine and the investigation of whether Capsazepine's antagonistic approach can be favorably utilized for defense utilization to block capsaicin-initiated pain and inflammation via the ocular pathway. Research design and methods: Ocular capsazepine in situ gels were prepared with polymers Pluronic F-127 and Chitosan; optimized formulation was quantified in ocular tissues chromatographically and by in vivo live ocular imaging; anti-inflammatory efficacy was determined by eye irritation testing, corneal and retinal imaging, ocular prostaglandin estimation, and by viability and proliferation testing using human ocular cell lines, etc. Results: A physicochemically stable Capsazepine in situ gel was formulated which showed little ocular irritation, considerable transcorneal permeation; was precisely quantified in ocular tissues by gas chromatography and in vivo live ocular imaging; showed anti-inflammatory properties against capsaicin by eye imaging experiments, prostaglandin declination and showed acceptable cytocompatibility when studied using human ocular cell lines. Conclusions: The fabricated in situ Capsazepine gel system might be promising for ocular delivery as it appears a pharmacologically potent and safe development, suitable for utilization in the ocular clinical therapy, provided there is additional research to substantiate it. Graphical Abstract: